Gender-associated role in patients with schizophrenia. Is there a connection with the resistance? - Panov, Georgi (Frontiers in Psychiatry, 2022)
Schizophrenia is a chronic mental illness observed with equal prevalence in different cultures and ethnic groups. The clinical picture relates to behavior and social adaptation. A significant percentage of patients, despite the implementation of various therapeutic interventions, remain resistant to the ongoing treatment. Occupying a certain gender role depends both on biological belonging and on the way of self-perception characteristic of the given person. Self-perception reflects gender identification, which in social aspect is determined by the choice of social activities performed. Changes in behavior and social adaptation in patients with schizophrenia led us to conduct a study to analyze the perceived gender role in patients with schizophrenia, looking for differences between patients with treatment resistance and those in clinical remission. Materials and methods A total of 105 patients with schizophrenia were analyzed. Of them, 45 were with resistant symptoms and 60 in clinical remission. The clinical analysis of the patients was carried out using the PANSS and BPRS scales. The evaluation of the choice of social activity related to a particular gender was done with the Bem Sex-Role Inventory (BSRI). Results Out of all 105 patients with schizophrenia, in 80/76.19%/we found a higher identification with the female role, 17/16.19%/made an association with the male role and in 8/7.61%/patients we found the same results, i.e., with both the male and female roles. Among the patients with treatment resistant schizophrenia (TRS)–45, 34/75.56%/identified more with the female gender role, 6/13.33/perceived the male gender role as active, and in 5/11.11%/the identification was equal both with the male and with the female roles. Among the patients in clinical remission (CR)–60, 46/76.67%/accepted the female role as active, 11/18.33/identified with the male one, and three/5%/accepted both roles equally. When assessing the relationship between biological sex and perceived gender role, it was found that among men/a total of 39/half identified with the female gender role and half with the male gender role. Among women/a total of 66/, 90% perceived the female gender role, 7%–the male and 3% equally the male and the female gender role. No relationship was found between the choice of a certain gender role and the onset of psychosis and its duration in the observed patients. Conclusion We found a higher percentage of schizophrenic patients who showed higher identification with the female gender role. Approximately half of the males identified with the female gender role. Resistance had no influence on the choice of sex-associated social activity. Factors related to the course of the schizophrenia process such as age of onset of psychosis and duration of psychosis was not associated with an influence on identification with sex-associated social activity. Our research suggests that identification with a particular sex associative social activity is most likely established earlier in the prodromal period.